46 Evaluation of management of lipid profile in high-risk PCI patients. (17th July 2020) - RAO, USHA; Narayanan, Deepa
Abstract : Aim: Dyslipidaemia is a major risk factor for development and progression of coronary arteriosclerosis. Low density lipoprotein-Cholesterol (LDL-C) concentration is strongly associated with an increase in atherosclerotic cardiovascular disease (CVD). Targeting LDL-C earlier significantly decreases the lifetime risk of CVD. Our main aim was to evaluate the management of lipids in high risk CVD patients admitted for PCI procedures at our tertiary centre. Methods: This was a retrospective study performed over a period of 1 month which included all the patients admitted for urgent, elective and primary PCI(PPCI) in our centre and they were followed up to 12 months thereafter. A detailed case note evaluation was performed including discharge summaries. Data collected include demographics, risk factors, reason for admission, procedure performed, lipid parameters and management, family history and follow up including outpatient (OP) appointments or admissions for repeat procedures, lipid levels and mortality over 12 months. Definitions: Treatment to target LDL-C was defined as LDL-C ≤ 2 mmol/L. Lipid thresholds for consideration of Simon Broome criteria for Familial Hypercholesterolaemia - Total cholesterol ≥ 7.5 mmol/L and /or LDL-C a level ≥ 4.9 mmol/L (pre-treatment). Results: A total of 101 patients (69 Male; 32 Female) were admitted for PCI procedures with a mean age of 65 years (42-90). They had multiple co-morbidities. Majority were admitted for PPCI (58, 57.4%) followed by NSTEMI (23, 22.4%) and elective (20, 19.8%) procedures Lipid profiles were unavailable for review in (32, 29.6%) patients (PPCI :14, NSTEMI :10 and electives:8). 37 patients had a Total Cholesterol of >5mmol/l(5-6.9) and 57 (56.4%) had an LDL level of > 2mmol/l (Mean LDL PPCI, 36: 3.1, NSTEMI, 10:3.1; Electives, 9:3.3). At the time of discharge, 97 patients were on statins, of whom 9 were on sub-optimum dose of statin and 4 statin naive. 5 patients fulfilled Simon Broome criteria for consideration of Familial Hypercholesterolaemia. High LDL group: In this group 65% had lipid profile tested for the first time at index admission and the rest (35%) though on statins had not been treated to target. Discharge summaries had insufficient information on family history of premature CAD, lipids on admission or treatment targets for primary care. As per our standard protocol, all patients post-PPCI and NSTEMI had one consultation in secondary care prior to being discharged to primary care. 12 months post PCI: Treatment target was achieved in 8(14%) patients, 7(12%) were not treated to target and 42(73%) of patients had no lipids available for comparison for the trend post-discharge. 27 (47%) events were recorded which included PCI:5; CABG:4; Angiograms:2, Death:4; PVD (peripheral vascular disease):4; Stroke:2; Permanent pacemaker insertion:1; OP appointments:4 (chest pain, breathlessness) At 12 months, 4 (7%) were not on any statins and 7 (12%) were on sub-optimum dose of statins. There were no referrals made to the Lipid Clinic. Conclusions: Our study showed that high-risk CVD patients were not adequately treated to target LDL-C concentrations. This highlights the need for education and increasing awareness of local guidelines and patient pathways for secondary prevention of CVD. We recommend a comprehensive discharge summary post-PCI inclusive of family history of premature heart disease, lipid levels and targets for treatment for the primary care . Conflict of Interest: None